Difficult or Complex Bile duct stones in ERCP: Large Balloon Dilation and other stone management methods. Accumulated experience in a referral Endoscopic Center 2009- 2018 - Yriberry Ureña, Simón (2021)
Introduction: Bile duct stones constitutes 20% of symptomatic gallbladder disease and difficult stones are one third of this. Endoscopic papillary large balloon dilation (EPLBD) with or without prior endoscopic sphincterotomy (EST) produces excellent outcomes for the treatment of complex or difficult common bile duct (CBD) stones, alone or combined with previous therapeutic options as mechanical lithotripsy (ML) and temporary or definitive stenting. Objectives: Show success rate, complications and adverse events. Show that higher success rates are obtained combining ERCP techniques with no increase in complications. Materials and methods: We evaluated the safety and therapeutic outcomes of EPLBD with vs. without EST and other combinations for the removal of difficult bile duct stones. We described our procedures for a decade and compare them with the previous decade without balloon dilation. Of 865 patients and procedures, 223 (25.78%) had difficult stones. Treatments where EPLBD with EST (n=183), EPLBD alone group (n=40). Additional modalities where required in 15.25% (n=34). These two groups were compared with respect to overall procedure-related adverse events, overall stone removal success rate, number of sessions required for complete stone removal, need for mechanical lithotripsy, temporal or definite stenting and total procedure time. Results: Safety removal of stones was achieved in one session on 84.75% of cases with EPLBD. The incidence of adverse events was not significantly different between the groups (EPLBD alone vs. EPLBD with EST: overall adverse events 12.5% vs. 10.38% (including pain); pancreatitis 2.7% vs. 2.5%, p=0.62). Overall success similar, initial success similar, and the need for additional techniques were also similar between groups. Median total procedure time tended to be greater in the EPLBD alone group (20.5 minutes) than in the EPLBD with EST group. Conclusion: DPBGD in ERCP allows bile duct stone extraction rates close to 99.65% (90% in previous decade) according to other reports of literature. Adverse events of EPLBD alone or with EST are similar between them and with classic ERCP without statistical difference and similar to other world series.